Attenuation of osteoarthritis progression via locoregional delivery of Klotho-expressing plasmid DNA and Tanshinon IIA through a stem cell-homing hydrogel - Peng Wang; Zhibo Zhao; Ziyang Li; Xiao Li; Benzhao Huang; Xiaoqing Lu; Shimin Dai; Shishuo Li; Zhentao Man; Wei Li (Journal of Nanobiotechnology, 2024)
Abstract Background Osteoarthritis (OA) is an aging-related degenerative joint disorder marked by joint discomfort and rigidity. Senescent chondrocytes release pro-inflammatory cytokines and extracellular matrix-degrading proteins, creating an inflammatory microenvironment that hinders chondrogenesis and accelerates matrix degradation. Targeting of senescent chondrocytes may be a promising approach for the treatment of OA. Herein, we describe the engineering of an injectable peptide-hydrogel conjugating a stem cell–homing peptide PFSSTKT for carrying plasmid DNA-laden nanoparticles and Tanshinon IIA (pPNP + TIIA@PFS) that was designed to attenuate OA progression by improving the senescent microenvironment and fostering cartilage regeneration. Results Specifically, pPNP + TIIA@PFS elevates the concentration of the anti-aging protein Klotho and blocks the transmission of senescence signals to adjacent healthy chondrocytes, significantly mitigating chondrocyte senescence and enhancing cartilage integrity. Additionally, pPNP + TIIA@PFS recruit bone mesenchymal stem cells and directs their subsequent differentiation into chondrocytes, achieving satisfactory chondrogenesis. In surgically induced OA model rats, the application of pPNP + TIIA@PFS results in reduced osteophyte formation and attenuation of articular cartilage degeneration. Conclusions Overall, this study introduces a novel approach for the alleviation of OA progression, offering a foundation for potential clinical translation in OA therapy.